O processo de terceirização do trabalho do assistente social nos serviços públicos - Assis, Selma Maria de (2011)
This dissertation aims to conduct a study on the social changes experienced in Brazil and the world from the 70s and its influence in the changing world of work, focusing on the phenomenon of outsourcing in the public sphere, particularly in relation established among social workers employed by Foundation Helio Augusto de Souza (Fundhas), and are assigned to work in the Social Development Secretariat (SDS) of the Municipality of São José dos Campos. The purpose of this paper is to explain how the changes resulting from global capital affect labor management in enterprises and within the state that seeks to reduce its operations and is to outsource part of their service. We seek to contextualize the contemporary settings of the crisis from the 70's, especially the military coup of 1964, which brought several implications for the Brazilian society and especially in social service who sought the re-conceptualization. We seek to explain how outsourcing becomes an adjustment to neoliberal capital more profits, the indicators of precariousness and its implications on the identities of professional and public sphere as the City of São José dos Campos has used this form of recruitment, the Ministry of Social Development and the repercussions of this relation in the professional identities and in dealing with the population. The knowledge of this vicious new form of employment contract, it is necessary not to fall in the complex plots of alienation / reification of the worker with the knowledge that professionals are inserted in the social division of labor and total social process.